Basic life support knowledge of family medicine residents at joint program of family medicine in Jeddah Saudi Arabia, 2017 - Fatani, Ammar A.; Johani, Nayef Al; Ibrahim, Adel M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Healthcare professionals are expected to have adequate knowledge of basic and advanced cardiac life support to revive unresponsive patients. Little is known about that in health care professionals in Saudi Arabia. Methods: we conducted this study in the joint program of family medicine to evaluate knowledge of physicians about basic life support, and to identify factors associated with the differences in their knowledge. Through a cross-sectional analytic study, all physicians in the Joint Program of Family Medicine in Jeddah were included in the study. For collection of data, a validated self-administered questionnaire was used. Results: Out of responding physicians (n=150), females constituted 117 (78%), their mean age accounted for 27.3±2.2 years. all physicians (99.3%) reported that they had attended BLS courses before. Out of a maximum of “13”, the mean score of correct answers accounted for 6.2±1.6, only 18.7% of the physicians achieved above average scores. Only qualification had statistically significant impact on the level of knowledge, the average score percentage was higher among those who have MBBS qualification only compared to their colleagues who have postgraduate degrees (48.3%±11.57% vs 39.2%±13.78%) p<0.05. Conclusions: Physicians in the Joint Program of Family Medicine have deficient level of knowledge about BLS, despite of their previous BLS training. Frequent training is strongly recommended to sustain adequate level of knowledge about BLS.